2016
DOI: 10.15376/biores.11.4.8806-8819
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Thermo-Chemical Degradation and Pyrolysis Properties for Three Kinds of Biomass Residues

Abstract: This study investigated the thermo-chemical degradation and fast pyrolysis of watermelon seed shells (WSS), pumpkin seed shells (PSS), and sunflower seed shells (SSS). The raw materials and pyrolysis products were analyzed. The results showed that the carbon content (52.96%), hydrogen content (7.38%) and higher heating value (HHV) (23.88 MJ/kg) of PSS were highest, and the bio-oil from the PSS pyrolysis had high amounts of phenolic compounds. For SSS, the content of holocellulose (83.47 wt.%) was the highest, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 20 publications
0
13
1
Order By: Relevance
“…A lower lignin value in our sample was expected based on the pre-treatment of the original material. Ash content was smaller than those previously reported [21,47], Phyllis database (https ://phyll is.nl/). In regard to the ultimate analysis of sunflower husks, values for C, H, N and S were within the range of those previously reported (C: 44-57.6 wt%, H: 5.6-6.5 wt%, N: 0.33-5.8 wt%, S: 0.05-0.31 wt%), while O was significantly lower (O: 41.4-49 wt%).…”
Section: Characterisation Of Raw Materialscontrasting
confidence: 69%
See 1 more Smart Citation
“…A lower lignin value in our sample was expected based on the pre-treatment of the original material. Ash content was smaller than those previously reported [21,47], Phyllis database (https ://phyll is.nl/). In regard to the ultimate analysis of sunflower husks, values for C, H, N and S were within the range of those previously reported (C: 44-57.6 wt%, H: 5.6-6.5 wt%, N: 0.33-5.8 wt%, S: 0.05-0.31 wt%), while O was significantly lower (O: 41.4-49 wt%).…”
Section: Characterisation Of Raw Materialscontrasting
confidence: 69%
“…Few reports have described the pyrolytic yields of SSS [47,76] with highly varying results depending on the initial feedstock composition, pyrolysis system and temperatures. For instance, pre-treated SSS (w/ Ganoderma lucidum) transformed in a static system at 400 °C produced almost identical amounts of biochar (27%), but higher bio-oil yields (34%) and lower gas content (39%) [17].…”
Section: Pyrolysis Of Biomassmentioning
confidence: 99%
“…This approach is similar to that followed by Pedersen et al 23 . The sunflower husk bio-oil components are taken from Liu et al 10 . The energy carrier is sand, at a sand to feedstock ratio of 22:1.…”
Section: Fast Pyrolysis Plantmentioning
confidence: 99%
“…Technologies that have been investigated for biofuel production from biomass include biological (fermentation, digestion) and thermochemical processes, such as combustion, gasification, pyrolysis, and hydrothermal liquefaction. It has been shown that sunflower husks are a promising 2G agricultural waste feedstock that is suitable for bio-oil production through fast pyrolysis 9,10 . The produced bio-oil could be used for the production of advanced biofuels 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Experimental work converting sunflower husks has been done on a laboratory or bench scale, , and simulation and technoeconomic assessments have been done on fast pyrolysis processing of corn stover and woody biomass feedstocks. ,, However, no published data can be found on the simulation and technoeconomic assessment of a sunflower husk value chain including fast pyrolysis and upgrading. To know whether this is a promising endeavor, the next step is to determine if upgraded bio-oil production from sunflower husks in a decentralized, hub-and-spoke distributed value chain is feasible.…”
Section: Introductionmentioning
confidence: 99%